Blood-pressure screening and supervision in general practice. Issue 6167 (31st March 1979) - Barber, J H; Beevers, D G; Fife, R; Hawthorne, V M; McKenzie, H M; Sinclair, R G; Simpson, R J; Stewart, G M; Williams, D I
Abstract : Since April 1975 all men aged 35-69 years registered with four general practices in west central Scotland have had their blood pressure checked whenever they visit the surgery. Although the practice locations range from rural to city centre and observers comprise receptionists, nurses, and doctors, a standard procedure has been adopted for the examination, recording, follow-up, and management of high blood pressure. The results confirm that raised blood pressure is common and often goes undetected. Even when hypertension is known, casual blood pressure readings often exceed accepted normal levels. The findings also show that a population may be routinely examined through normal contact with the family doctor, and that this can provide a convenient, acceptable, and effective means of detecting and reducing raised blood pressure.